PA / HDPE composite material capable of being used for high-voltage insulator and preparation method of PA / HDPE composite material

By adding polyamide to high-density polyethylene and using irradiation crosslinking technology, the PA/HDPE composite material is formed, which solves the problem of poor mechanical properties and heat resistance of high-density polyethylene in high-pressure insulators, and a significant performance improvement is achieved.

CN119552437APending Publication Date: 2025-03-04中广核俊尔(浙江)新材料有限公司 +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411611767.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

As a general plastic, high-density polyethylene has problems with poor mechanical properties and heat resistance in high-pressure insulators.

Method used

Using PA/HDPE composite material, the three-dimensional hybrid structure is formed by adding PA6 to HDPE and irradiation crosslinking technology to improve the mechanical and heat resistance of the material.

Benefits of technology

It significantly improves the comprehensive mechanical properties and instantaneous heat resistance of high-voltage insulators, and the local instantaneous high-temperature resistance can reach 250-350℃, improving the safety of use.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a PA6 / HDPE composite material capable of being used in the field of high-voltage insulators and a preparation method of the PA6 / HDPE composite material. The composite material is mainly prepared from the following raw materials in percentage by weight: 10-60% of HDPE (High-Density Polyethylene); 10 to 20% of PA6 (polyamide 6); 5-10% of a compatilizer; 15-25% of a compound flame retardant; 10-15% of an inorganic filler; 0.5-5% of a stabilizer; 1-3% of a crosslinking auxiliary agent; and 0.1-3% of a lubricant. The preparation method comprises the following steps: premixing the raw materials at a high speed, extruding, granulating and carrying out injection molding through a double-screw extruder, and carrying out irradiation modification on the raw materials by adopting electron beams to obtain the expected high-voltage insulator. After the material is subjected to electron beam irradiation modification, the comprehensive performance, especially the weather resistance and the instantaneous heat resistance, of the material is greatly improved, and the problem that a single HDPE thick product is prone to shrinkage and pore forming is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high molecular polymer alloy material and a preparation method thereof, which can be specifically used in the field of high voltage power transmission. Background Art

[0002] At present, the types of high-voltage insulator materials that can be used in power are mainly ceramics, glass and composite materials. Ceramics and glass have high density and brittleness, which leads to high manpower, material and energy consumption in actual use. At the same time, they will produce a lot of dust emissions, which is not conducive to environmental protection.

[0003] Composite insulators are divided into inorganic composite insulators and organic composite insulators. Among them, organic composite insulators currently mainly include: ethylene propylene rubber, silicone rubber, polytetrafluoroethylene, epoxy resin, etc. Compared with inorganic insulators, organic composite insulators have the advantages of light weight, high insulation, strong surface hydrophobicity, and good anti-pollution flashover performance. However, rubber and epoxy resin products have the disadvantages of poor machinability, poor recyclability, complex processing technology, long processing cycle, and high energy consumption.

[0004] Thermoplastics are a type of plastic that is plastic at a certain temperature, solidifies after cooling, and can repeat this process. This can greatly improve the processability and plasticity of the product. At the same time, plastic products have very excellent electrical insulation and are expected to become a new type of high-voltage insulator material. For example, CN106046772A discloses a low-temperature and UV-resistant PA6 / HDPE alloy material.

[0005] High-density polyethylene is expected to become a new generation of high-voltage insulator materials due to its high crystallinity, non-polarity, odorlessness, non-toxicity, good chemical stability, cold resistance, insulation, heat resistance and strong comprehensive performance. For example, CN109929168A discloses a modified polyethylene material suitable for power insulators and its preparation method. Its formula consists of the following components: polyethylene 50-65%, toughening agent 2-6%, inorganic filler 15-20%, brominated flame retardant 15-20%, synergistic flame retardant 1.5-5%, stabilizer 0.6-1.4%, coupling agent 0.5-1%, lubricant 0.2-1%. Although this material can meet the current basic requirements for insulators, it still has defects such as low mechanical properties, insufficient instantaneous heat resistance, and poor long-term weather resistance, which will seriously affect its actual performance in outdoor use.

[0006] Irradiation cross-linking technology refers to the technology of realizing macromolecular cross-linking reaction through high-energy electron beam irradiation, which transforms linear polymers into polymers with three-dimensional spatial network structure. This technology can improve the mechanical properties, chemical resistance, electrical properties, heat resistance (instantaneous heat resistance) and weather resistance of products. Summary of the invention

[0007] The present invention aims to solve the defects of poor mechanical properties and heat resistance of high-density polyethylene itself as a general-purpose plastic, and provides a PA / HDPE composite material that can be used for high-voltage insulators and a preparation method thereof. The material is based on PA / HDPE alloy, and can be granulated by conventional thermoplastic molding methods, and then the injection molded parts are further irradiated and modified. The entire production process is green and simple, and the obtained material has excellent local instantaneous high temperature resistance and electrical properties.

[0008] The present invention achieves the above-mentioned purpose of the invention by the following technical means.

[0009] A PA / HDPE composite material that can be used for high-voltage insulators and a preparation method thereof, characterized in that it is composed of the following raw materials in percentage by weight: HDPE: 10-60% PA6: 10-20% Compatibilizer: 5-10% Compound flame retardant: 15-25% Inorganic filler: 10-15% Stabilizer: 0.5-5% Cross-linking agent: 1-3% Lubricant: 0.1-3%.

[0010] The HDPE is selected from pure HDPE or a compound of HDPE and other types of PE, and other types of PE include but are not limited to one or more of LLDPE, LDPE, UHWPE, etc., wherein the melt index of HDPE is 0.3-50 g / 10min, 230°C / 2.16 kg; preferably 0.5-5 g / 10min; preferably HDPE produced by a Phillips-type catalyst and having a medium-width molecular weight distribution.

[0011] The PA is pure PA6 or PA6 compounded with other types of PA, and other types of PA include but are not limited to one or more of PA66, PA12, PA56, copolymerized PA66 / 6, etc., wherein the melt index of PA6 is 5-40g / 10min, 250°C / 2.16 kg; preferably 15-25g / 10min.

[0012] The compatibilizer is one or a combination of ethylene-acrylic acid polymer (EAA); ethylene-octene copolymer (POE); ethylene-octene copolymer grafted with maleic anhydride (POE-g-MAH); ethylene-propylene diene rubber (EPDM); ethylene-propylene diene rubber grafted with maleic anhydride (EPDM-g-MAH); ethylene-vinyl acetate copolymer (EVA), preferably EAA, wherein the AA content is between 10-40%.

[0013] The composite flame retardant is one of a bromine-antimony system, a phosphorus-nitrogen system and a silicon-phosphorus system; preferably a bromine-antimony system; wherein the bromine-based flame retardant can be one or more of brominated triazine, brominated epoxy, decabromodiphenyl ethane, brominated polystyrene, tetrabromobisphenol A, octabromoether, decabromodiphenyl ether and octabromodiphenyl ether; wherein the antimony provider is one or more of antimony oxide and antimonate.

[0014] The inorganic filler can be one or more of mica powder, calcium carbonate, talc, wollastonite, alumina, kaolin, bentonite, synthetic magnesium silicate, and zinc oxide; preferably talc, calcium carbonate, and mica powder; wherein the mesh size is between 800-3000 mesh, and the powder can also be in the form of a masterbatch.

[0015] The stabilizer is composed of one or more of an antioxidant, a flame retardant stabilizer and a light stabilizer; wherein the antioxidant can be one or more of a hindered phenol antioxidant or a phosphite antioxidant; the hindered phenol antioxidant is antioxidant 1010 or antioxidant 1098; the phosphite antioxidant is antioxidant 168; the flame retardant stabilizer can be one or more of di-n-butyltin dilaurate, di-n-butyltin thioglycolate, di-n-octyltin dilaurate or di-n-octyltin thioglycolate. The light stabilizer can be one or more of an ultraviolet absorber or a hindered amine stabilizer, preferably the two are compounded, and the compounding ratio is preferably 1:2-1:4.

[0016] The cross-linking aid is one or more of triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethylallyl isocyanurate (TMAIC), trimethylolpropane trimethacrylate (TMPTMA), and ethylene glycol dimethacrylate (EGDMA).

[0017] The lubricant is selected from one or more of silicone lubricant, silicone oil, zinc stearate, sodium stearate, calcium stearate, pentaerythritol stearate, ethylene bisstearamide, polyethylene wax, oxidized polyethylene wax, ethylene-acrylic acid copolymer, and montan acid wax.

[0018] The material preparation and processing method comprises the following steps: melt extrusion granulation by a twin-screw extruder, the screw speed being 250-450 rpm / min, the extruder temperature being 170-300°C, the resin and the powder being melt-blended and then extruded for granulation, wherein the cross-linking aid can be introduced through the main feed or side feed of the extruder screw, or can be introduced in the form of external mixing of finished particles and cross-linking aid masterbatch.

[0019] The crosslinking method is selected from heat-induced crosslinking, light-induced crosslinking, chemical-induced crosslinking and high-energy ray irradiation crosslinking, preferably irradiation crosslinking, wherein the irradiation ray is an electron beam or a gamma ray, and the irradiation dose is 25-300 kGy.

[0020] This product can add different types of color powder to achieve specific color effects according to customer needs.

[0021] Compared with the prior art, the present invention has the following innovative advantages: 1. The present invention adds engineering plastic PA6 to HDPE, thereby greatly improving the defects of polyethylene as a general plastic in high-voltage insulators, such as low comprehensive mechanical properties and insufficient heat resistance, while retaining the advantages of high-density polyethylene, such as chemical resistance and high insulation.

[0022] 2. The present invention reduces the proportion of carbon atoms in the material by adding PA6 to HDPE, effectively reduces the amount of flame retardant added, and meets green and environmental protection requirements.

[0023] 3. The present invention adopts radiation cross-linking technology to simultaneously cross-link the two components in the alloy to form a three-dimensional hybrid structure, which can effectively improve the comprehensive performance of high-voltage insulators in practical applications, especially their instantaneous heat resistance. Its local instantaneous heat resistance can reach 250-350°C without softening, which greatly improves the safety of high-voltage insulators.

[0024] 4. Due to its high crystallinity and fast crystallization rate, HDPE is prone to holes, cracks and bubbles during the molding process. This defect increases the risk of high-voltage breakdown of plastic insulators and poses a safety hazard. Adding PA6 can effectively improve the occurrence of this defect. DETAILED DESCRIPTION

[0025] The following provides examples to further illustrate the invention. It is necessary to declare that the following examples cannot be understood as limiting the scope of protection of the invention. If technicians in this field make some non-essential improvements and adjustments to the invention based on the above-mentioned content of the invention, they still fall within the scope of protection of the invention.

[0026] The extrusion granulation implementation process includes the following processes: Before extrusion, HDPE and PA6 were dried in an oven at 80°C for 12 h.

[0027] After drying, weigh each component material according to the ratio in Table 1 and pour it into a high-speed mixer for uniform mixing.

[0028] The specific proportions of Examples 1-5 and Comparative Examples 1-3 are shown in Table 1 below, with the raw materials being expressed in mass percentage: raw material(%) Example 1 Example 2 Example 3 Example 4 Example 5 Comparison sample 1 Comparison sample 2 Comparison sample 3 HDPE 40 40 40 40 40 0 60 40 PA6 10 12.5 15 17.5 20 60 0 20 Maleic Anhydride Grafted EPDM 5 5 5 5 5 5 5 5 Compound flame retardant 28 25.5 23 20.5 18 18 18 18 Inorganic fillers 13 13 13 13 13 13 13 13 Stabilizer 2 2 2 2 2 2 2 2 Crosslinking aid 1 1 1 1 1 1 1 1 Lubricants 1 1 1 1 1 1 1 1 The compound flame retardant in the table is a compound of decabromodiphenylethane and antimony trioxide, and the compounding ratio is 3:1; the inorganic filler is talcum powder; the stabilizer is a compound of 168, 1010 and UV5411, and the compounding ratio is 3:2:1; the lubricant is calcium stearate; the crosslinking aid is: triallyl isocyanurate (TAIC); Examples 1 to 5 use Phillips-type catalysts to produce HDPE with a medium-width molecular weight distribution, a product of Chevron Phillips Chemical; Comparative sample 3 uses a titanium-alkyl aluminum catalyst to produce HDPE with a narrow molecular weight distribution, a commercially available product produced by a domestic petrochemical plant Ziegler-Natta catalyst.

[0029] After the above components are mixed evenly, they are mixed and extruded through a twin-screw extruder with an extrusion temperature of 240-260° C. and a main engine speed of 350-380 rpm / min.

[0030] After extrusion, it is water cooled and pelletized.

[0031] After granulation, injection molding is performed to prepare samples, and the injection molding temperature is 240-260°C.

[0032] The injection molded parts are irradiated and cross-linked in an electron beam (10 MeV) with an irradiation dose of 25-300 kGy, preferably 100 kGY.

[0033] The various performance tests were conducted according to the corresponding test standards, mainly focusing on the performance tests before and after irradiation (0 kGy and 100 kGy). The specific experimental results are shown in Table 2 below.

[0034] Performance Indicators Test Standards Test Unit Example 1 Example 1 Example 2 Example 2 Example 3 Example 3 Example 4 Example 4 Example 5 Example 5 Comparison sample 1 Comparison sample 1 Comparison sample 2 Comparison sample 2 Comparison sample 3 Comparison sample 3 Radiation dose (kGy) - - 0 100 0 100 0 100 0 100 0 100 0 100 0 100 0 100 Tensile Strength GB / T 1040.2-2006 Mpa 20.5 33.2 25.4 34.5 30.2 40.1 33.3 48.5 37.1 50 51.1 64.7 18.9 29.6 37.3 46.4 Bending Strength GB / T 9341.1-2008 Mpa 23.9 39.9 25.1 42.1 31.5 51.1 38.5 57.2 40.3 71.5 60 86.7 31.5 41.8 42.6 53.0 Flexural modulus GB / T 9341.1-2008 Mpa 1138 1816 1116 2099 1316 2041 1521 2335 1820 3100 2388 4200 1316 2057 1880 2100 Notched impact strength GB / T 1043.1-2008 <![CDATA[kJ / m 2 ]]> 3.4 3.3 3.7 2.7 4.2 4.2 4.4 4.3 4.8 4.1 5.5 4.8 4.2 2.7 4.8 4.5 Unnotched impact strength GB / T 1043.1-2008 <![CDATA[kJ / m 2 ]]> 15 24 13 20 22 30 24 32 26 35 30 23 22 14 27 32.5 Flame retardant grade GB / T 2408-2008 / V0 V0 V0 V0 V0 V0 V1 V0 V1 V0 V0 V0 HB V1 V1 V0 Hot needle test (Φ2mm, 350℃*60s) / um X <5 X <5 X <5 X <5 X <5 X <5 X <5 X 300 Note: In the hot needle test, X means that the object melted instantly when the hot needle touched it.

[0035] Comparing Examples 1-5 with Comparative Example 2, the results show that with the addition of PA6, the tensile, bending and other mechanical properties of the composite material are significantly increased.

[0036] Comparing Example 5 with Comparative Example 3, the results show that the HDPE produced by different methods used in the present invention has a significant difference in performance improvement after irradiation.

[0037] Comparing the non-irradiated sample (0 kGy) and the irradiated sample (100 kGy) of each embodiment, the results show that the mechanical properties, flame retardancy and thermal properties of the product after irradiation cross-linking are better than those of the non-irradiated sample.

[0038] Comparing Examples 1-5, the results show that as the PA6 content increases, the amount of flame retardant corresponding to the same flame retardant level decreases, which means that the amount of flame retardant required to achieve the goal can be reduced, which is conducive to cost reduction.

[0039] Based on the above performances, it can be seen that Examples 3-4 can meet the mechanical, flame retardant and thermodynamic properties required by high-voltage insulators.

Claims

1. A PA / HDPE composite material that can be used for high voltage insulators, characterized in that The following raw materials are used in percentage by weight composition: HDPE: 10-60% PA6: 10-20% Compatibilizer: 5-10% Compound flame retardant: 15-25% Inorganic filler: 10-15% Stabilizer: 0.5-5% Cross-linking agent: 1-3% Lubricant: 0.1-3%.

2. The PA / HDPE composite material for high voltage insulators according to claim 1, characterized in that: The HDPE is selected from pure HDPE or a compound of HDPE and other types of PE. The HDPE is produced by a Phillips-type catalyst and has a medium-width molecular weight distribution.

3. The PA / HDPE composite material for high voltage insulators according to claim 1, characterized in that: The PA6 is pure PA6 or a mixture of PA6 and other types of PA.

4. The PA / HDPE composite material for high voltage insulators according to claim 1, characterized in that: The compatibilizer is one of ethylene-acrylic acid polymer (EAA); ethylene-octene copolymer (POE); ethylene-octene copolymer grafted with maleic anhydride (POE-g-MAH); ethylene-propylene diene monomer rubber (EPDM); ethylene-propylene diene monomer rubber grafted with maleic anhydride (EPDM-g-MAH); ethylene-vinyl acetate copolymer EVA, or a combination of several of them.

5. The PA / HDPE composite material for high voltage insulators according to claim 1, characterized in that: The compound flame retardant is one of a bromine antimony system, a phosphorus nitrogen system and a silicon phosphorus system; the inorganic filler is one or more of mica powder, calcium carbonate, talcum powder, wollastonite, alumina, kaolin, bentonite, synthetic magnesium silicate and zinc oxide.

6. The PA / HDPE composite material for high voltage insulators according to claim 1, characterized in that: The stabilizer is compounded by an antioxidant, a flame retardant stabilizer, and an ultraviolet absorber, wherein the antioxidant is one or more of a hindered phenol antioxidant or a phosphite antioxidant; the flame retardant stabilizer is one or more of di-n-butyltin dilaurate, di-n-butyltin thioglycolate, di-n-octyltin dilaurate, or di-n-octyltin thioglycolate; and the light stabilizer is one or more of an ultraviolet absorber or a hindered amine stabilizer.

7. The PA / HDPE composite material for high voltage insulators according to claim 1, characterized in that: The selected crosslinking aid is one or more of triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethylallyl isocyanurate (TMAIC), trimethylolpropane trimethacrylate (TMPTMA), and ethylene glycol dimethacrylate (EGDMA).

8. The PA / HDPE composite material for high voltage insulators according to claim 1, characterized in that: The lubricant is one or more of silicone lubricant, silicone oil, zinc stearate, sodium stearate, calcium stearate, pentaerythritol stearate, ethylene bis stearamide, polyethylene wax, oxidized polyethylene wax, ethylene-acrylic acid copolymer, and montan acid wax.

9. A method for preparing a PA / HDPE composite material that can be used for high voltage insulators, comprising the following steps: After the filler is surface treated, each component is added to a high-speed premixer in proportion and evenly mixed, and then extruded into granules using a twin-screw extruder, the screw speed is 250-400 rpm / min, and the extruder temperature is between 170-300°C; the cross-linking aid is added in the form of main feeding, side feeding, masterbatch and / or external mixing of the extruder screw, and the obtained material is dried, further injection molded and irradiated to obtain the above-mentioned PA / HDPE composite material that can be used for high-voltage insulators.

10. The method for preparing a PA / HDPE composite material for high voltage insulators according to claim 9, characterized in that: The irradiation treatment uses high-energy electron beams or gamma rays, and the irradiation dose is 25-300 kGy.

Citation Information

Patent Citations

  • Low-temperature-resistant and ultraviolet-resistant PA6 / HDPE (polyamide 6 / high-density polyethylene) alloy material

    CN106046772A

  • Thermoplastic modified polyethylene material suitable for electric insulators, and preparation method thereof

    CN109929168A

  • Weatherable irradiation crosslinking cable material

    CN102660108A

  • HDPE (high-density polyethylene) power cable material with high dielectric strength and insulativity and preparation method of HDPE power cable material

    CN105542288A

  • Enhanced type polyamide / polyolefin alloy material and preparation method thereof

    CN107383864A